السياحة الذكية من منظور مفاهيمي: Smart tourism from a conceptual perspective - سلوى كربوش; عبد الحفيظ مسكين (Journal of North African Economies, 2025)
The term "smart tourism" is a modern and complex concept in the tourism sector. Smart tourism is a new development for tourism as a result of the impact of information technology on the tourism sector as a whole. This study aimed to capture the conceptual framework of smart tourism, some associated terminology and the difference between it and e-tourism. As a new term, there are few studies on it, especially in Arabic, When the theoretical aspect is taken to clarify its meaning more, with reference to smart cities their characteristics and technologies, Smart tourism destination and its relationship to both smart tourism and smart cities.